2019
DOI: 10.1111/exd.13881
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential for rosacea therapeutics of siRNA dispersion in topical emulsions

Abstract: Rosacea is a prevalent skin condition dependent on the individual genetic profile. The current pharmacological management of this condition is mostly based on small molecule drugs predominately effective in ameliorating the inflammatory condition. Emerging molecular approaches could present an opportunity for managing rosacea conditions at transcriptomic level, and in the future allow personalized approaches. RNA medicines, such as small RNA interference (siRNA), could provide a flexible and applicable tool re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Considerable evidence has shown that lipophilic liposomes and cream formulations are capable of delivering large molecules to the hair follicles, which promote transdermal delivery in conjunction with sebaceous glands and facilitate the distribution of macromolecules within the dermis ( Dokka et al, 2005 ) - ( Colombo et al, 2019 ). Previous research has reported that the topical application of an emulsified siRNA on the skin surface can lead to the efficient suppression of the target gene in the epidermis, and this can be further improved by the addition of a penetration-enhancing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has shown that lipophilic liposomes and cream formulations are capable of delivering large molecules to the hair follicles, which promote transdermal delivery in conjunction with sebaceous glands and facilitate the distribution of macromolecules within the dermis ( Dokka et al, 2005 ) - ( Colombo et al, 2019 ). Previous research has reported that the topical application of an emulsified siRNA on the skin surface can lead to the efficient suppression of the target gene in the epidermis, and this can be further improved by the addition of a penetration-enhancing agent.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, Colombo et al developed a small RNA interference (siRNA) that targets TLR2 and applied emulsified siRNA to the inner and outer surface of mice ears in the presence of active excipients, such as glycerol/urea. This resulted in a significant decrease in TLR2 levels, indicating the potential for siRNA to manage rosacea at the transcriptional level [ 299 ]. These findings suggest that such drugs may represent the future direction of rosacea management.…”
Section: Treatmentsmentioning
confidence: 99%
“…SiRNA technologies have a strong ability to suppress gene expression with a high target specificity, and there are many reports related to siRNA applications as new therapeutic drugs for intractable diseases, including cancer, , amyloidosis, , and immune diseases. , Although siRNAs are expected to become a new generation of therapeutic drugs as nucleic acid medicines owing to their strong gene-suppression effects and ease of use, several problems, such as cellular delivery, poor nuclease resistance, and various side effects (off-target effects and interferon responses at high concentrations), must be solved before they can be applied in the clinic. To solve the problems associated with siRNAs, many chemically modified siRNAs have been developed to improve the properties of siRNAs. With regard to chemically modified siRNAs, there have been reports of modifications on the sugar moiety, such as 2′-modifications, a locked nucleic acid, , and 4′-thioDNA or 4′-thioRNA, modifications to the phosphate backbone, such as phosphorothioate, , boranophosphate, and morpholino oligonucleotides, and modifications to base moieties, such as triazole and ethynyl nucleobase derivatives. , These chemical modifications to siRNA resulted in a higher nuclease resistance and a strong gene suppression with reduced off-target effects.…”
Section: Introductionmentioning
confidence: 99%